2021
DOI: 10.5371/hp.2021.33.3.140
|View full text |Cite
|
Sign up to set email alerts
|

How Does Iron Deficiency Anemia Impact Outcomes following Revision Total Hip Arthroplasty?

Abstract: Purpose Studies have shown the prevalence of iron deficiency anemia (IDA) increasing worldwide, and currently the literature is limited on the impact of IDA on outcomes following revision total hip arthroplasty (RTHA). Therefore, the purpose of this study was to determine whether IDA patients undergoing RTHA have longer: 1) in-hospital lengths of stay (LOS); 2) medical complications; and 3) costs of care. Materials and Methods A retrospective query of a nationwide admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It is also associated with adverse postoperative outcomes. According to the findings of the study, [7] patients with hip fractures who also had anemia experienced prolonged hospitalization, increased prevalence of POP, and higher hospitalization expenses. Previous studies have reported that preoperative anemia is present in 12.8% to 24.3% of patients undergoing hip and knee arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…It is also associated with adverse postoperative outcomes. According to the findings of the study, [7] patients with hip fractures who also had anemia experienced prolonged hospitalization, increased prevalence of POP, and higher hospitalization expenses. Previous studies have reported that preoperative anemia is present in 12.8% to 24.3% of patients undergoing hip and knee arthroplasty.…”
Section: Introductionmentioning
confidence: 99%